1982
DOI: 10.1002/jso.2930200416
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma

Abstract: Hemangiopericytoma is a rare soft tissue tumor with unpredictable biological behavior and with a high local recurrence rate. Wide surgical excision of all lesions, whenever feasible, should be the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 11 publications
0
39
0
1
Order By: Relevance
“…Our 5-and 10-year disease-specific survivals were 89 and 73%, respectively. Historically, hemangiopericytomas have been reported to have a worse prognosis than solitary fibrous tumor, with 5-and 10-year hemangiopericytoma survival rates as low as 59 and 47-70%, respectively, 3,15 and up to 48% disease-specific mortality. 16 In pleural solitary fibrous tumor, recurrence and mortality are reportedly predicted by both histology and resectability; typically, benign pedunculated tumors excised with clear margins have a recurrence rate of 2%, while sessile malignant solitary fibrous tumors may recur up to 63% of the time, resulting in a 30% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our 5-and 10-year disease-specific survivals were 89 and 73%, respectively. Historically, hemangiopericytomas have been reported to have a worse prognosis than solitary fibrous tumor, with 5-and 10-year hemangiopericytoma survival rates as low as 59 and 47-70%, respectively, 3,15 and up to 48% disease-specific mortality. 16 In pleural solitary fibrous tumor, recurrence and mortality are reportedly predicted by both histology and resectability; typically, benign pedunculated tumors excised with clear margins have a recurrence rate of 2%, while sessile malignant solitary fibrous tumors may recur up to 63% of the time, resulting in a 30% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of 60 patients, McMaster et al 18 found that 48% had died of disease. Of the19 patients reported by Auguste et al, 19 53% developed pulmonary metastases; the overall survivals were 59% and 47% at 5 and 10 years, respectively. Such a wide spread in reported outcome suggests a lack of uniform pathologic criteria in these studies.…”
Section: Discussionmentioning
confidence: 82%
“…These are clearly divergent survival data as compared to those previously reported. 4,18,19 We believe that this substantial difference in survival is due to our use of immunohistochemistry and electron microscopy in a multimodal pathologic review to exclude other soft tissue tumors histologically mimicking conventional HPC. The vastly different experience of improved overall survival for this cohort as compared to the literature is an important observation.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its vascular ity and, when large enough in the pelvis or retroperitoneal space, it Hemangiopericytoma may occur anywhere that capillaries are found, although the most common sites are the lower extremities and pelvis. There is an equal male-to-female ratio and it can occur at any age [6,[11][12][13]15]. The most common clinical presentation of this rare tumor is a painless expanding mass.…”
Section: Discussionmentioning
confidence: 99%